Case report: Pancreatic cancer-the insidious disease - Đurić, Aleksandar; Lovrenski, Aleksandra; Škrbić, Dušan; Radić, Jelena; Marjanović, Marko (Archive of Oncology, 2024)
Pancreatic cancer is one of the most aggressive forms of malignant disease, often with a long asymptomatic course, early metastases to distant organs and with an extremely poor prognosis.Here we present the case of a 70-year-old female patient, who was hospitalized in a pulmonology institution with a severe general condition. Due to bilateral lung changes seen on the chest radiograph, she was under suspicion for pneumonia, respiratory insufficiency and had elevated markers of inflammation. On physical examination, paraumbilically on the right, a subcutaneous swelling had been palpated with a harder consistency measuring 7 cm in diameter. She presented an ulcerated umbilicus with a purulent discharge. Nineteen hours after admission, a fatal outcome occurred and the autopsy proved an extended malignant disease (pancreatic ductal adenocarcinoma (aT3N2M1, Stage IV)) with multiple metastases.  It is necessary to adhere to the differential diagnostic algorithm of bilateral lung lesions. Each umbilical nodule should arouse suspicion of the existence of malignant diseases in the abdominal-pelvic region. Therefore, it is of great importance to raise people's awareness about taking control of their health.
Keywords: pancreatic carcinoma; Sister Mary Joseph's nodule; bilateral pneumonia